PERBANDINGAN HASIL BELAJAR MODEL TWO STAY TWO STRAY DENGAN THINK PAIR SHARE - Windi Oktaviana; Ilmiyati Rahmy Jasril (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to determine the significant differences between the Two Stay Two Stray (TSTS) and Think Pair Share (TPS) learning models on student learning outcomes at SMK N 1 Padang. This study uses a Pre-experimental research method with one-group pretest-posttest design. The sample selection is done by Probability sampling technique with simple random sampling. The sample in this study students of class X TAV B as the experimental class I and class X TAV C as the experimental class II. Data collection techniques were obtained from the results of posttest as many as 25 multiple choice questions. Obtained the average value of the experimental class I was 84.8 and experimental class II was 77. Based on the results of the hypothesis test, the value of tcount = 2.48 and ttable = 2.024, because tcount> ttable after Ho was rejected and Ha was accepted. It can be concluded that there is a significant difference between the use of TSTS and TPS cooperative models on the learning outcomes of students of Basic Electricity and Electronics in class X SMK N 1 Padang. Keywords: Learning Model, Two Stay Two Strays, Think Pair Share, Learning Outcomes.